Combine any like terms in the expression. If there are no like terms, rewrite the expression.
1 answer:
Answer:
4t
Step-by-step explanation:
Note that teach term has the variable t in it. Also, note that if t is by itself, it actually means 1t. Combine the given constants:
5t + 1t - 2t
= (5t + 1t) - 2t
= (6t) - 2t
= 4t
4t is your answer.
~
You might be interested in
Answer:
I need info
Step-by-step explanation:
4 (k+3) (k+) is the answer
Answer:
Choice B
Step-by-step explanation:
7.1×10⁵ = 710,000
That easy just divide 9 by 22 if need simplify it